Alkaline stress disrupts growth, biochemistry, and ion homeostasis of chickpea (Cicer arietinum L.) roots - Kumar, Kundan; Jaiswal, Arti; Koppolu, Uma Mahendra Kumar; Kumar, Koppolu Raja Rajesh (Frontiers in Agronomy, 2024)
Alkaline stress imposes significant constraints on agriculture by reducing nutrient availability and inhibiting plant growth. This study examines the physiological and biochemical responses of chickpea (Cicer arietinum L.) seedlings to alkaline stress, with implications for improving crop resilience. Chickpea seedlings were subjected to combined Na₂CO₃ and NaHCO₃ treatments, and changes in growth, root morphology, and nutrient uptake were evaluated. Alkaline stress led to substantial reductions in growth metrics (shoot and root length, fresh and dry weights), root-to-shoot ratio, and lateral root number, indicating pronounced root damage. This damage was associated with elevated hydrogen peroxide (H₂O₂) levels, increased membrane damage, and reduced cell viability. In response to alkaline stress, chickpea roots accumulated osmolytes (proline, soluble sugars) and upregulated antioxidant enzymes (catalase, ascorbate peroxidase) as an adaptive response to mitigate osmotic and oxidative stress. Ion homeostasis was disrupted, with decreased uptake of essential nutrients like K, P, Mn, Fe, and Zn, while the uptake of Na, Mg, and Ca increased, disturbing nutrient balance. These findings underscore the need for strategies, such as genetic improvement to enhance alkaline stress tolerance in chickpea, contributing to improved crop performance in challenging soil conditions.